Tahlil MaÃ¡yir Taâ€™lim al-QiraÃ¡h li al-Nathiqin bi Ghairih fi al-Ãrb wa al-Gharb (Rusyd Ahmad ThuÃ¡imah, al-Majlis al-Imriki li Taâ€™lim al-Lughat al-Ajnabiyyah wa al-Majlis al-Urubiy li Taâ€™lim al-Lughat al-Ajnabiyyah) - Zainuddin, Ammar; Asrori, Imam; Huda, Miftahul (Institut Agama Islam Negeri Curup, 2022)
This article aims to examine international language standards that may be used as references for teaching Arabic in institutions other than madrasas. The author chose Rusydi Ahmad Thu'aimah, ACTFL and CEFR as materials for standardizing foreign language teaching because there is no doubt about the quality and fame of the three standards. It's just that there must be common ground and differences between each of the three standards. The standardization of Arabic teaching in madrasas has been determined by the publication of KMA number 183 of 2019. This guide contains how to implement the Arabic Arabic curriculum in madrasah. However, the next question is what about the guidelines or standardization of Arabic teaching in public schools, Islamic boarding schools, and course institutions in Indonesia Thus, this research is theoretical in nature more towards conceptual. And to get the conceptual answer, the researcher uses a qualitative approach with qualitative content analysis methods and is a documentary study with the primary sources being the works of Rusydi Ahmad Thu'aimah, the ACTFL guidelines and the CEFR guidelines. The results of this study indicate that there is no tafÄul teaching (interaction) in the ACTFL and CEFR guidelines and this is the uniqueness of Rusydi Ahmad Thu'aimah's standard. While the uniqueness of ACTFL compared to others is the division of novice, intermediate, and advance standards into three parts. While CEFR has a distinctive importance for teaching texts that are more communicative and contextual, such as teaching text in the form of letters and the importance of an image in the text. The implication of this finding is that the standardization of foreign language teaching needs to be integrated into one use for teaching Arabic language outside madrasah.